Social Support on Life Satisfaction: A Meta-Analysis Study - Zefanya Kapoyos; Jusuf Tjahjo Purnomo (Universitas PGRI Yogyakarta, 2026)
The present meta-analytic study investigates the relationship between social support and life satisfaction by synthesizing findings from diverse empirical studies across cultural, age, and methodological contexts. A total of nine peer-reviewed studies published between 2015 and 2025 were included, comprising 5,035 participants from varied demographic backgrounds. A random-effects model was fitted in Jamovi to account for potential heterogeneity across studies. The analysis revealed a significant positive correlation between social support and life satisfaction (r = 0.525, p < 0.001). Considerable heterogeneity was observed (I² = 90.98%), suggesting substantial variability in effect sizes. Despite this, the direction and magnitude of the association remained consistent. No significant publication bias was detected, indicating the robustness of the findings. These results highlight social support as a critical predictor of life satisfaction and psychological well-being across different stages of life. The study underscores the importance of fostering supportive social environments in both clinical and community settings. Keywords: social support, life satisfaction, meta-analysis